Analysis of beach volleyball action sequences of femal top athletes - Koch, C.; Tilp, M. (Journal of Human Sport & Exercise, 2009)
The purpose of the study was to investigate sequences of typical beach volleyball actions to determine action patterns and anticipate athlete's behaviour. Videos from 18 games including 1645 action sequences consisting of 10918 actions from female World Tour athletes were analyzed. Single actions were recorded in a data base and probabilities of serve-reception, set-attacking, and reception-attacking action sequences were determined by means of data base queries. Chi-square tests were applied to determine significant patterns. Results did not reveal any superior type of serve which would create difficulties for the receiving team (p>0.05). The type of attack (smash or shot) did not significantly depend on the position of the setting. However, there was a tendency (p=0.054) to hard attacks when the ball was preceded by a setting far away from the net of from a lateral position near the side lines. The temporal position within a rally did neither effect the type nor the quality of attack (p>0.05). Contrariwise, the quality of the preceding reception did influence the type (p < 0.01) and the quality (p < 0.05) of attack. Following "good" receptions athletes preferred hard attacks and were more effective compared to situation where they had "perfect" or "poor" receptions. Although dependencies could not be detected in all analyzed cases the analysis of beach volleyball action sequences even by simple means of probabilities is a promising method to determine tactical patterns in beach volleyball.